Dari Menabung ke Berinvestasi: Program Peningkatan Literasi Keuangan dan Intensi Investasi Siswa MA Al Ulya Al Mubarok - Saeful Fachri; Mila Nurmila; Emilia Sari; Rahmah Febriyanti; Intan Permatasari (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
The main problem faced by MA Al Ulya Al Mubarok is the low level of financial literacy and the lack of understanding of the importance of early investment. Most students still perceive saving as the only form of financial management without recognizing the potential for asset growth through safe and well-planned investments. The absence of practical education on personal financial management and limited access to learning resources about investment are the main barriers to developing intelligent and future-oriented financial behavior. As a solution, this community service program is designed to improve financial literacy and foster investment intention among students. The program will be implemented through several stages of activities, including: needs and baseline analysis of students, development of a contextual-based financial literacy module, interactive socialization and training on the basic concepts of saving, personal financial management, and introduction to investment. The expected outcomes of this program include: an increase in students’ financial literacy level by at least 30% based on pre-test and post-test results, the initiation of a student investment awareness community, and the creation of a financial literacy learning module that can be used sustainably by the school. This community service program is expected to serve as a model for financial literacy development in secondary education institutions while supporting national efforts to build a financially literate, independent, and future-oriented young generation.